Status of glucose metabolism including insulin resistance and beta cell function in overtly iron loaded Thalassemia patients - Pan, A; Nag, SS; Mondal, BC; Anindya Dasgupta, A; Piyali Mitra, P (Journal of College of Medical Sciences-Nepal, 2015)
BACKGROUND Abnormality of glucose metabolism is a frequent complication in Thalassemia patients. Both insulin deficiency and insulin resistance has been proposed in its pathogenesis. Some form of abnormality in glucose metabolism is expected at an earlier age in these patients in developing countries like India and Nepal where iron overload is excessive due to lack of chelation therapy. MATERIALS AND METHODS Fasting serum glucose and fasting serum insulin (FSI) were measured in 40 beta-thalassemia major patients, 40 Ebeta- thalassemia patients and 40 controls, all aged between 5 and 12 years. 2 hours after an appropriate dose of oral glucose feed (Children ingested 1.75 g/kg body weight maximum 75 gram dissolved in 250 to 300 ml water) blood samples were drawn again to measure post prandial serum glucose. Iron overload was assessed by measuring liver size, spleen size, total amount of packed cells transfused and serum ferritin. Insulin resistance (IR), insulin sensitivity (%S) and beta cell functions (%B) were derived from the measured laboratory parameters using the latest version of Homeostatic Model Assessment (HOMA) calculator software. RESULTS No one had impaired glucose metabolism or diabetes mellitus beta-thalassemia major patients showed evidence of insulin resistance in the form of significantly higher fasting serum insulin (p value 0.002), IR (p value 0.003), %B (p value 0.017) and significantly lower %S (0.002) when compared with controls. FSI showed positive correlation with total amount of packed cells received (r=0.372, p=0.018), serum ferritin (r=0.345, p=0.029) and spleen size (r=0.427, p=0.006). Similarly, IR also showed positive correlation with total amount of packed cells received (r=0.388, p=0.013), serum ferritin (r=0.336, p=0.034) and spleen size (r=0.425, p=0.005). %S showed negative correlation with all these parameters. %B didn’t show any statistically significant correlation with these parameters.Ebeta- thalassemia patients didn’t have any statistically significant difference in FSI, IR, %S and %B than controls. CONCLUSION Insulin resistance develops as the earliest abnormality in glucose metabolism in overtly iron loaded beta thalassemia major patients at an early age. Ebeta- thalassemia patients with milder phenotype do not develop dysfunction of glucose metabolism at such an early age. Journal of College of Medical Sciences-Nepal, 2014, Vol-10, No-3, 29-36